(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Production of meat and meat products is one of the key segments of domestic processing industry. In 2018, its share in total food production in Ukraine reached 17.78% (vs. 15.93% in 2013). At the same time, the main problem holding back the development of this segment is the reduction of the raw material base for the industrial processing of meat due to the crisis in animal husbandry, especially in pig and cattle breeding. The purpose of the article is to define the current state, trends and prospects of increasing the capacity of meat production in the regions of Ukraine. According to the results of research, during 2014-2018 the total volume of meat procurement by livestock farms in Ukraine decreased by 1.41%. The cuts in procurement were characteristic for all types of meat except poultry. Accordingly, chicken dominates the structure of procured meat (with a share of 53.46% in 2018) and in the structure of industrial meat production (57.36%). Despite the reduction of the raw material base, there is a gradual increase in meat production in Ukraine. Thus, in 2018, 87.81% of raw materials procured by agricultural producers were sent for processing (vs. 82.11% in 2013). However, only the five regions specialize in meat products, meaning that in their meat production structures the advanced meat processing is dominated. Based on the differentiation of the regions of Ukraine by the scale of raw material procurement and meat production, it is determined that the vast majority (15) of regions do not have significant potential in this segment of the economy. The meat procurement and meat industrial production are highly concentrated in the territories – in 2018, 54.67% of meat and 64.51% of meat products were produced in five regions (Vinnytsia, Dnipro, Kyiv, Lviv and Cherkasy). Despite the negative trends in the production of meat and meat products in general, there has been a positive foreign trade balance of these goods since 2014 in Ukraine. The current global economic environment offers significant opportunities for increasing Ukrainian exports of chicken and other niche poultry meat. With the increase in livestock, the prospects for increasing external supplies of pork and beef are promising.